2010
DOI: 10.1111/j.1468-0394.2010.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic particle filter: applying abstraction techniques to the design of visual tracking algorithms

Abstract: Many real-world visual tracking applications have a high dimensionality, i.e. the system state is defined by a large number of variables. This kind of problem can be modelled as a dynamic optimization problem, which involves dynamic variables whose values change in time. Most applied research on optimization methods have focused on static optimization problems but these static methods often lack explicit adaptive methodologies. Heuristics are specific methods for solving problems in the absence of an algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Building on their work in Pantrigo and Sanchez 61 and Pantrigo et al, 62 Cabido et al 63 show an e®ective approach to visual tracking on a graphical processing unit using a hybridized particle¯lter. They propose a hybridization of the particle¯lter with a memetic algorithm to form the memetic algorithm particle¯lter (MAPF) for tracking single and multiple objects.…”
Section: Hybrid and Metaheuristic Particle¯ltersmentioning
confidence: 98%
“…Building on their work in Pantrigo and Sanchez 61 and Pantrigo et al, 62 Cabido et al 63 show an e®ective approach to visual tracking on a graphical processing unit using a hybridized particle¯lter. They propose a hybridization of the particle¯lter with a memetic algorithm to form the memetic algorithm particle¯lter (MAPF) for tracking single and multiple objects.…”
Section: Hybrid and Metaheuristic Particle¯ltersmentioning
confidence: 98%
“…Furthermore, including the LS procedure into the PF framework results in a more flexible algorithm. In fact, the statespace defined in the PF stage can be different from the search space used in the LS stage (Pantrigo et al, 2011). This is very useful in visual tracking problems, and we make use of this feature in the present work.…”
Section: Tracking Modulementioning
confidence: 99%
“…The similarities between particle filters and evolutionary algorithms have been known and exploited by many researchers [17]. Patrigo et al [17] recently suggested a framework for combining particle filters with population based metaheuristics for visual articulated motion tracking. Later in 2007, Uosaki et al [20] proposed an evolutionary strategies particle filter (ESP) for the fault detection in dynamic system.…”
Section: Introductionmentioning
confidence: 99%